Preparation method of high-precision three-dimensional silicon structure

Through the double -photon aggregation 3D printing technology and magnesium heat reduction reaction, POSS uses POSS as a photoresist, solving the problem of difficulty in preparing high -precision sub -silicon structures for high -precision sub -micron -level silicon structures, and realizing high -precision, fast, and economical silicon structure preparation Essence

CN119370850AActive Publication Date: 2025-01-28SOUTHEAST UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411498753.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and economically prepare high-precision submicron-scale three-dimensional silicon structures. The traditional method relies on large equipment, with many steps and high time and economic costs.

Method used

Use POSS with POSS with a optical solidification substitution base as a photoretimeter with the use of the twin -optical aggregation 3D printing technology. The 3D model of the software is designed and the printing path is planned to obtain the high -precision initial POSS model. Remove the excess light carvings, then sinter at high temperature to remove organic ingredients, and finally obtain the silicon structure of the sub -micron level accuracy through magnesium heat reduction reactions.

Benefits of technology

The three -dimensional silicon structure of high -precision sub -micron -level three -dimensional silicon structure is realized, and the problems of expensive equipment and many steps in traditional methods can be avoided, and the purpose of high -precision and rapidly creating any complex silicon structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370850A_ABST
    Figure CN119370850A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-precision three-dimensional silicon structure, which comprises the following steps of: (1) establishing a 3D model of a silicon structure to be printed through software, planning a printing path, and printing in a two-photon polymerization 3D printer by using TPL photoresist to obtain an initial POSS (Polyhedral Oligomeric Silsesquioxane) model; (2) soaking the obtained model in propylene glycol methyl ether acetate, removing unpolymerized photoresist, taking out the model, soaking the model in isopropanol, and removing propylene glycol methyl ether acetate to obtain a POSS model; (3) sintering the POSS model in a high-temperature air atmosphere to remove organic components in the POSS model so as to obtain a silicon dioxide model; and (4) carrying out reduction reaction on the silicon dioxide model and magnesium powder in a high-temperature argon atmosphere, and reducing silicon dioxide into silicon to obtain a silicon structure with submicron precision.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-precision three-dimensional silicon structure. Background Art

[0002] 3D printing technology is a new manufacturing technology developed in the 1980s. This technology does not require molds during the processing process. You can directly use software to design a virtual model, and then directly obtain a physical model in the printing device through a layer-by-layer accumulation method. The principle of 3D printing based on photocuring is as follows: liquid 3D photoresist rapidly undergoes photopolymerization reaction under light of a certain wavelength and intensity, and the molecular weight increases sharply, turning from liquid to solid. After removing the excess liquid photoresist, the remaining solid part is the obtained physical model. This technology not only has the processing capability of any complex structure, but also has the advantages of rapid prototyping, high design freedom, and material saving compared to traditional manufacturing methods. Two-photon polymerization 3D printing (TPL) is one of the most accurate printing technologies, which can achieve sub-micron resolution. Such high manufacturing accuracy and design freedom without molds make TPL printing technology one of the choices for people to quickly prepare small objects with precise structures.

[0003] However, the development of TPL printing is constrained by some conditions, such as the limited choice of photoresists. At present, most of the models manufactured by TPL printing are organic materials such as photosensitive resins and hydrogels, and there are few reports and applications of TPL printing to manufacture inorganic component models. Silicon is the main material for manufacturing semiconductor devices. Modern electronic devices, such as computers, smart phones, and tablets, all rely on silicon-based integrated circuits. Sensors and actuators in micro-electromechanical systems are widely used in automobiles, medical equipment, consumer electronics and other fields, and also rely on high-precision silicon structures. Therefore, silicon materials are of great significance to industrial development. At present, the methods for preparing submicron silicon structures are relatively complex, mainly including photolithography, etching and chemical vapor deposition. Photolithography is the most common method, which defines the pattern on the silicon wafer by using light. High-resolution photolithography technologies such as deep ultraviolet (DUV) lithography and extreme ultraviolet (EUV) lithography can achieve submicron and nanometer resolution. Etching methods are divided into dry and wet methods. Using plasma etching materials can achieve high anisotropic etching, which is suitable for making vertical sidewall structures. Chemical reagent etching is suitable for the preparation of larger-scale silicon structures, and the resolution and processing aspect ratio are greatly limited. Chemical vapor deposition deposits thin films on silicon wafers, and then forms fine structures through subsequent photolithography and etching processes. The above methods often rely on large equipment, have many steps, and are time- and economically expensive, making them unsuitable for the rapid preparation of three-dimensional micro-nano silicon structures. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a high-precision three-dimensional silicon structure, which can quickly prepare a silicon structure with submicron precision.

[0005] Technical solution: The method for preparing a high-precision three-dimensional silicon structure of the present invention comprises the following steps:

[0006] (1) Using software to establish a 3D model of the silicon structure to be printed and plan the printing path, use TPL photoresist to print in a two-photon polymerization 3D printer (printed on a quartz substrate), and obtain a high-precision initial POSS model;

[0007] (2) soaking the obtained model in propylene glycol methyl ether acetate until the unpolymerized photoresist is completely washed away, taking it out and then soaking it in isopropanol until the propylene glycol methyl ether acetate is completely washed away, thereby obtaining a POSS model;

[0008] (3) placing the POSS model in a high-temperature air atmosphere for sintering to remove the organic components in the POSS model, and the entirety of the POSS model undergoes isotropic shrinkage during the sintering process to obtain a high-precision silicon dioxide model;

[0009] (4) The silica model and magnesium powder are subjected to a reduction reaction in a high-temperature argon atmosphere to reduce the silica to silicon, thereby obtaining a silicon structure with submicron line spacing and characteristic size (in Example 1, the spacing between two adjacent lines in the structure is equivalent to the resolution of the display screen, and the characteristic size refers to the width of the lines in the structure, which is equivalent to the pixel size).

[0010] Wherein, in step (1), during the printing process, the laser power is 5 to 50 mW / cm 2 , the printing speed is 300~15000μm / s.

[0011] Among them, in step (1), the 3D printer is a two-photon laser direct writing 3D printer, and the light source of the printing device excites the photoinitiator. Under the action of the free radicals generated by the photoinitiator, a photopolymerization reaction rapidly occurs between the propyl acryloyloxy groups on the periphery of the POSS, and the molecular weight increases rapidly from a liquid state to a solid state, thereby generating a solid POSS model, in which the silicon oxygen core of the POSS is also included.

[0012] Wherein, in step (1), the TPL photoresist is composed of the following components in parts by weight: 75 to 99 parts of POSS with a photocurable substituent, 0 to 20 parts of a diluent, and 1 to 5 parts of a photoinitiator.

[0013] The POSS with a photocurable substituent is octaacryloxypropyl POSS; the diluent is polyethylene glycol diacrylate; and the photoinitiator is 4,4′-bis(diethylamino)benzophenone.

[0014] The preparation method of TPL photoresist is as follows: POSS with photocurable substituents, diluent and photoinitiator are mixed in a formulated amount, stirred evenly under light-proof conditions of room temperature to 50°C, to obtain TPL photoresist and store it in a light-proof environment at 4°C.

[0015] Wherein, in step (2), the mixture is immersed in propylene glycol methyl ether acetate for 10 to 15 minutes and immersed in isopropanol for 10 to 15 minutes.

[0016] Wherein, in step (3), the sintering temperature is 700-800° C., and the sintering time is 2-2.5 hours.

[0017] The heating rate is 2-10°C / min, and the cooling rate is 2-10°C / min to room temperature.

[0018] Wherein, in step (4), the mixing mass ratio of the silica model and the magnesium powder is 1:10 to 15. The silica model and magnesium powder of not less than ten times the mass are placed in a sealed stainless steel sample boat for reduction reaction.

[0019] Wherein, in step (4), the temperature of the reduction reaction is 650-700° C., and the reaction time is 4-5 h.

[0020] The heating rate is 2-5°C / min, and the cooling rate is 5-6°C / min to room temperature.

[0021] The photoresist used in the present invention mainly comprises POSS with a photocurable substituent, which can form a hybrid model of polymerized organic-inorganic components under the action of free radicals generated by a photoinitiator; after obtaining a primary POSS model, the organic part is removed by high-temperature treatment, and the whole model is isotropically shrunk to obtain a silicon dioxide structure, and a magnesium thermal reduction reaction is performed to obtain a silicon structure that is isotropically shrunk again, thereby achieving the purpose of high-precision 3D printing of silicon structures.

[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the method of the present invention uses cage-type polysilsesquioxane (POSS) with polymerizable substituents as the main component of the photoresist, and uses two-photon laser direct writing (TPL)

[0023] The 3D printing technology is used to prepare a high-precision POSS model, and then the organic components are removed by high-temperature treatment to obtain a silicon dioxide structure, and finally the required silicon structure with submicron precision is obtained by magnesium thermal reduction reaction. Compared with the traditional etching process, the present invention can quickly prepare silicon structures with submicron precision, achieving the purpose of high-precision and rapid manufacturing of any complex silicon structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the principle diagram of the method of the present invention;

[0025] Figure 2 This is a model diagram of the silicon structure to be printed in Example 1;

[0026] Figure 3 The scanning electron microscope images of the structures obtained at various stages in the method of Example 1;

[0027] Figure 4 EDS element analysis of samples obtained at various stages of the method in Example 1;

[0028] Figure 5 XPS element chemical state analysis of the silicon dioxide structure and silicon structure before and after magnesium thermal reduction treatment in the method of Example 1; A) Si chemical state; B) O chemical state; C) Mg chemical state; D) C chemical state;

[0029] Figure 6 This is a model diagram of the silicon structure to be printed in Example 2 and the submicron precision silicon hollow spherical structure obtained after printing;

[0030] Figure 7 This is a modeling diagram of the silicon structure to be printed in Example 3 and the submicron precision diatom-shaped structure obtained after printing. DETAILED DESCRIPTION

[0031] Example 1

[0032] The method for preparing a high-precision three-dimensional silicon structure of the present invention comprises the following steps:

[0033] The target model is a line structure with a line period of 1.2μm and a feature size of 120nm. The modeling software is used to design a line structure with a lateral period of 2μm, such as Figure 2 shown.

[0034] (1) preparing TPL photoresist: by weight, 99 parts of octaacryloxypropyl POSS and 1 part of 4,4′-bis(diethylamino)benzophenone were mixed, and heated to 40° C. in a light-proof environment using a constant temperature magnetic stirring device and stirred until a uniform state was achieved, thereby preparing TPL photoresist for use;

[0035] (2) Printing was performed using the TPL photoresist prepared in step (1) in a two-photon polymerization 3D printer (model: Nanoscribe Photonic Professional GT) with a laser power of 20 mW / cm 2 , the printing speed is 3000 μm / s, and the initial model is obtained;

[0036] (3) The obtained model was immersed in propylene glycol methyl ether acetate and taken out after 10 minutes; then immersed in isopropanol and taken out after 10 minutes, and the excess photoresist was removed to obtain a POSS line structure with a line period of 1.94 μm and a line width of 223 nm. Figure 3 As shown in A;

[0037] (4) The POSS line structure was sintered in an air atmosphere, the temperature was raised at a rate of 5°C / min, and after reaching 700°C, it was maintained for 2 h, and then cooled to room temperature at a rate of 5°C / min to obtain a proportionally reduced silicon dioxide line structure with a line period of 1.16 μm and a line width of 118 nm. Figure 3 As shown in B;

[0038] (5) The obtained silicon dioxide line structure sample and excess magnesium powder (the mixing mass ratio of silicon dioxide line structure and magnesium powder is 1:10) are placed in a sealed stainless steel sample boat for magnesium thermal reduction. The reaction atmosphere is argon gas, the heating rate is 2°C / min, and after reaching 650°C, it is maintained for 4 hours, and then cooled to room temperature at 5°C / min to obtain a submicron precision silicon line structure with a line spacing of 1.02μm and a feature size of 105nm. Figure 3 As shown in C, the requirements of the target model are met.

[0039] like Figure 4 As shown, EDS elemental analysis was performed on the POSS structure, silica structure and silicon structure obtained in Example 1. The results showed that after sintering and magnesium thermal reduction treatment, carbon and oxygen elements were removed, proving that the structure composed of silicon was successfully obtained.

[0040] like Figure 5 As shown, XPS elemental chemical state analysis was performed on the silica structure and the silicon structure. Figure A shows that the chemical state of Si before magnesium thermal reduction belongs to SiO2 (103.5 eV), and it is converted into Si element (99.4 eV) after the reduction reaction; Figure B shows that the chemical state of O before magnesium thermal reduction belongs to SiO2 (532.9 eV), and the O intensity decreases significantly after the reduction reaction; Figure C shows that after magnesium thermal reduction, no Mg residue was detected on the surface of the product (Mg metal, Mg oxide 1303-1304.5 eV); Figure D shows trace C residue or external contamination (CC peak 284.8 eV).

[0041] Comparative Example 1

[0042] The target model is a line structure with a line period of 1.2μm and a feature size of 120nm. The modeling software is used to design a line structure with a lateral period of 2μm, such as Figure 2 shown.

[0043] (1) preparing TPL photoresist: by weight, 99 parts of octaacryloxypropyl POSS and 1 part of 4,4′-bis(diethylamino)benzophenone were mixed, and heated to 40° C. in a light-proof environment using a constant temperature magnetic stirring device and stirred until a uniform state was achieved, thereby preparing TPL photoresist for use;

[0044] (2) Printing was performed using the TPL photoresist prepared in step (1) in a two-photon polymerization 3D printer (model: Nanoscribe Photonic Professional GT) with a laser power of 30 mW / cm 2 , the printing speed is 3000 μm / s, and the initial model is obtained;

[0045] (3) The obtained model was immersed in propylene glycol methyl ether acetate and taken out after 10 minutes; then immersed in isopropanol and taken out after 10 minutes, and the excess photoresist was removed to obtain a POSS line structure with a line period of 1.97 μm and a line width of 358 nm;

[0046] (4) Sintering the POSS line structure in an air atmosphere, heating at a rate of 5°C / min, maintaining at 700°C for 2h, and then cooling to room temperature at a rate of 5°C / min to obtain a proportionally reduced silicon dioxide line structure with a line period of 1.17 μm and a line width of 192 nm;

[0047] (5) The obtained silica line structure sample and excess magnesium powder (the mixing mass ratio of silica line structure and magnesium powder is 1:10) are placed in a sealed stainless steel sample boat for magnesium thermal reduction. The reaction atmosphere is argon. The heating rate is 2°C / min. After reaching 650°C, it is maintained for 4 hours and then cooled to room temperature at 5°C / min to obtain a submicron precision silicon line structure with a line spacing of 1.08μm and a feature size of 167nm.

[0048] Compared with Example 1, due to the increase in laser intensity, the polymerization area is enlarged, the lines are widened, the feature size is increased by about 59.04%, and the line spacing is increased by about 5.88%. The accuracy is lower than that of Example 1 and does not meet the target model requirements.

[0049] Comparative Example 2

[0050] The target model is a line structure with a line period of 1.2μm and a feature size of 120nm. The modeling software is used to design a line structure with a lateral period of 2μm, such as Figure 2 shown.

[0051] (1) preparing TPL photoresist: by weight, 99 parts of octaacryloxypropyl POSS and 1 part of 4,4′-bis(diethylamino)benzophenone were mixed, and heated to 40° C. in a light-proof environment using a constant temperature magnetic stirring device and stirred until a uniform state was achieved, thereby preparing TPL photoresist for use;

[0052] (2) Printing was performed using the TPL photoresist prepared in step (1) in a two-photon polymerization 3D printer (model: Nanoscribe Photonic Professional GT) with a laser power of 20 mW / cm 2 , the printing speed is 2500μm / s, and the initial model is obtained;

[0053] (3) The obtained model was immersed in propylene glycol methyl ether acetate and taken out after 10 minutes; then immersed in isopropanol and taken out after 10 minutes, and the excess photoresist was removed to obtain a POSS line structure with a line period of 2.01 μm and a line width of 273 nm;

[0054] (4) Sintering the POSS line structure in an air atmosphere, heating at a rate of 5°C / min, maintaining at 700°C for 2h, and then cooling to room temperature at a rate of 5°C / min, to obtain a proportionally reduced silicon dioxide line structure with a line period of 1.21 μm and a line width of 144 nm;

[0055] (5) The obtained silica line structure sample and excess magnesium powder (the mixing mass ratio of the silica line structure and the magnesium powder is 1:10) are placed in a sealed stainless steel sample boat for magnesium thermal reduction. The reaction atmosphere is argon. The heating rate is 2°C / min. After reaching 650°C, it is maintained for 4 hours and then cooled to room temperature at 5°C / min to obtain a submicron precision silicon line structure with a line spacing of 1.05μm and a feature size of 130nm.

[0056] Compared with Example 1, due to the reduction in scanning speed, the diffusion rate of free radicals decreased, and the free radical concentration per unit volume increased, resulting in an increase in the polymerization area, making the lines wider, resulting in a 27.45% increase in feature size and an increase in line spacing of approximately 2.94%. The accuracy decreased compared with Example 1 and did not meet the target model requirements.

[0057] Example 2

[0058] The target model is a hollow spherical structure with a diameter of 30 μm and a characteristic size of 400 nm. The structure is designed using modeling software such as Figure 6 As shown in A.

[0059] (1) preparing TPL photoresist: by weight, 90 parts of octamethacryloxypropyl POSS, 9 parts of ethylene glycol dimethacrylate and 1 part of 4,4′-bis(diethylamino)benzophenone were mixed, and heated to 40° C. in a light-proof environment using a constant temperature magnetic stirring device and stirred until a uniform state was achieved, thereby preparing TPL photoresist for use;

[0060] (2) Printing was performed using the TPL photoresist prepared in step (1) in a two-photon polymerization 3D printer (model: Nanoscribe Photonic Professional GT) with a laser power of 5 mW / cm 2 , the printing speed is 300μm / s, and the initial model is obtained;

[0061] (3) The obtained model was immersed in propylene glycol methyl ether acetate and taken out after 10 minutes; then immersed in isopropanol and taken out after 10 minutes, and the excess photoresist was removed to obtain a POSS hollow spherical structure with a diameter of 40.76 μm and a characteristic size of 669 nm;

[0062] (4) The POSS hollow spherical structure was sintered in an air atmosphere, the temperature was increased at a rate of 2°C / min, and after reaching 700°C, it was maintained for 2 h, and then cooled to room temperature at a rate of 5°C / min, to obtain a proportionally reduced hollow spherical structure with a diameter of 32.49 μm and a characteristic size of 434 nm;

[0063] (5) The obtained hollow spherical structure sample and excess magnesium powder (the mixing mass ratio of the hollow spherical structure and magnesium powder is 1:10) are placed in a sealed stainless steel sample boat for magnesium thermal reduction. The reaction atmosphere is argon gas, the heating rate is 2°C / min, and after reaching 650°C, it is maintained for 4h, and then cooled to room temperature at 5°C / min to obtain a submicron precision silicon hollow spherical structure with a diameter of 28.51μm and a characteristic size of 382nm, as shown in FIG. Figure 6 As shown in B, the requirements of the target model are met.

[0064] Example 3

[0065] The target model is a diatom-shaped structure with a size of 40*25*10μm and a feature size of 500nm. The structure is designed using modeling software such as Figure 7 As shown in A.

[0066] (1) preparing TPL photoresist: by weight, 90 parts of octamethacryloxypropyl POSS, 9 parts of polyethylene glycol diacrylate and 1 part of 4,4′-bis(diethylamino)benzophenone were mixed, and heated to 40° C. in a light-proof environment using a constant temperature magnetic stirring device and stirred until a uniform state was achieved, thereby preparing TPL photoresist for use;

[0067] (2) Printing was performed using the TPL photoresist prepared in step (1) in a two-photon polymerization 3D printer (model: Nanoscribe Photonic Professional GT) with a laser power of 50 mW / cm 2 , the printing speed is 15000μm / s, and the initial model is obtained;

[0068] (3) The obtained model was immersed in propylene glycol methyl ether acetate and taken out after 15 minutes; then immersed in isopropanol and taken out after 15 minutes, and the excess photoresist was removed to obtain a POSS diatom-shaped structure with an overall size of about 60*40*15 μm;

[0069] (4) sintering the POSS diatom-shaped structure in an air atmosphere, heating at a rate of 2°C / min, maintaining at 700°C for 2h, and then cooling to room temperature at a rate of 5°C / min, to obtain a proportionally reduced diatom-shaped silica structure;

[0070] (5) The obtained diatom-shaped silica structure sample and excess magnesium powder (the mixing mass ratio of the structure and magnesium powder is 1:15) are placed in a sealed stainless steel sample boat for magnesium thermal reduction. The reaction atmosphere is argon gas, the heating rate is 5°C / min, and after reaching 650°C, it is maintained for 5h, and then cooled to room temperature at 5°C / min to obtain a diatom-shaped structure with an overall size of approximately 38.52*24.42*9.58μm and a characteristic size of 482nm. Figure 7 As shown in B, the requirements of the target model are met.

Claims

1. A method for preparing a high-precision three-dimensional silicon structure, characterized in that: The steps include: (1) Establishing a 3D model of the silicon structure to be printed and planning the printing path through software, and printing it in a two-photon polymerization 3D printer using TPL photoresist to obtain an initial POSS model; (2) soaking the obtained model in propylene glycol methyl ether acetate to remove the unpolymerized photoresist, taking it out and then soaking it in isopropanol to remove the propylene glycol methyl ether acetate to obtain a POSS model; (3) placing the POSS model in a high temperature air atmosphere for sintering to remove the organic components in the POSS model to obtain a silicon dioxide model; (4) The silicon dioxide model and magnesium powder are subjected to a reduction reaction in a high-temperature argon atmosphere to reduce the silicon dioxide to silicon, thereby obtaining a silicon structure with submicron precision.

2. The preparation method according to claim 1, characterized in that: In step (1), during the printing process, the laser power is 5 to 50 mW / cm 2 , the printing speed is 300~15000μm / s.

3. The preparation method according to claim 1, characterized in that: In step (1), the TPL photoresist is composed of the following components in parts by weight: 75 to 99 parts of POSS with a photocurable substituent, 0 to 20 parts of a diluent, and 1 to 5 parts of a photoinitiator.

4. The preparation method according to claim 3, characterized in that: The POSS with a photocurable substituent is octaacryloxypropyl POSS or octamethacryloxypropyl POSS; the diluent is polyethylene glycol diacrylate or ethylene glycol dimethacrylate; and the photoinitiator is 4,4′-bis(diethylamino)benzophenone.

5. The preparation method according to claim 1, characterized in that: In step (2), soak in propylene glycol methyl ether acetate for 10 to 15 minutes; soak in isopropyl alcohol for 10 to 15 minutes.

6. The preparation method according to claim 1, characterized in that: In step (3), the sintering temperature is 700-800° C. and the sintering time is 2-2.5 hours.

7. The preparation method according to claim 6, characterized in that: The heating rate is 4-5°C / min; the cooling rate is 4-5°C / min to room temperature.

8. The preparation method according to claim 1, characterized in that: In step (4), the mixing mass ratio of the silica model and the magnesium powder is 1:10 to 15.

9. The preparation method according to claim 1, characterized in that: In step (4), the temperature of the reduction reaction is 650-700° C., and the reaction time is 4-5 h.

10. The preparation method according to claim 9, characterized in that: The heating rate is 2-5°C / min; the cooling rate is 5-6°C / min to room temperature.

Citation Information

Patent Citations

  • Honeycomb porous silicon / carbon composite material and preparation method thereof

    CN105958047A

  • Honeycomb 3D porous silicon material and preparation method thereof

    CN106115710A

  • Preparation and application of 3D (Three-dimensional) printing photosensitive resin containing POSS (Polyhedral Oligomeric Silsesquioxane)

    CN108117624A

  • Method for compressing and optimizing surface roughness of inscribed structure based on axial resolution

    CN118259558A